2022
DOI: 10.1107/s1600576722001686
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional recurrence relations and Takagi–Taupin equations. I. Dynamical X-ray diffraction by a perfect crystal

Abstract: The dynamical diffraction of spatially restricted X-ray beams in a thick perfect crystal is studied using two-dimensional recurrence relations and the Takagi–Taupin (T-T) equations. It is shown that the two-dimensional recurrence relations are transformed into T-T equations when passing from a crystal with an array of discrete lattice planes to a model of continuous periodic electron density. The results of calculations of the X-ray diffraction field inside the crystal and the angular distribution of the scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The coefficient ' ¼ 2�d=ð� sin � B Þ in the 2D recurrence relations takes into account the phase difference that occurs when an X-ray beam propagates in a periodic structure from one node to another on a network in the procedure of numerical calculations. It has recently been shown that 2D recurrence relations transform into T-T equations when passing from a discrete layered structure to a model of a periodic medium with a continuous electron density (Punegov & Kolosov, 2022). It is noted that, in some cases, calculations of X-ray fields using the T-T equations can be unstable, but calculations using 2D recurrence relations are always stable.…”
Section: Equations Of X-ray Diffraction In a Bent Crystalmentioning
confidence: 99%
“…The coefficient ' ¼ 2�d=ð� sin � B Þ in the 2D recurrence relations takes into account the phase difference that occurs when an X-ray beam propagates in a periodic structure from one node to another on a network in the procedure of numerical calculations. It has recently been shown that 2D recurrence relations transform into T-T equations when passing from a discrete layered structure to a model of a periodic medium with a continuous electron density (Punegov & Kolosov, 2022). It is noted that, in some cases, calculations of X-ray fields using the T-T equations can be unstable, but calculations using 2D recurrence relations are always stable.…”
Section: Equations Of X-ray Diffraction In a Bent Crystalmentioning
confidence: 99%
“…В настоящее время разработаны вычислительные методы картографирования интенсивности когерентного рассеяния в обратном пространстве с использованием двумерных рекуррентных соотношений (ДРС) [5,6] и уравнений Такаги−Топена [7]. Недавно показано, что ДРС и уравнения Такаги−Топена в случае динамической дифракции рентгеновских лучей в совершенном кристалле идентичны и полностью совпадают при переходе от дискретно-слоистой структуры к модели периодической среды с непрерывной электронной плотностью [8]. При этом было установлено, что численные расчеты на основе ДРС всегда устойчивы, в то время как вычисления с применением уравнений Такаги−Топена в ряде случаев дают неустойчивые решения.…”
unclassified
“…2) составляет L x = xd = 1.3 mm. Дифракционное рентгеновское поле пространственно ограниченной волны в изогнутом многослойном зеркале преимущественно формируется внутри трапеции ABCD при условии равенства размеров падающего и дифрагированного пучков [8]. Процедура вычислений карт RSM с использованием ДРС изложена в [5,8].…”
unclassified